The genus Clerodendrum (Lamiaceae) in the flora of Central Africa (D.R. Congo, Rwanda, Burundi) - Meerts, Pierre (Phytotaxa, 2023)
The revision of the genus Clerodendrum in D.R. Congo, Rwanda and Burundi is presented. Thirty-three taxa are accepted (28 species, 4 varieties, 1 form). Two new varieties are described (Clerodendrum capitatum var. pubitubum, Clerodendrum johnstonii var. rubropunctatum). Two new synonyms are proposed. A neotype is designated for C. buchneri, C. buettneri, C. fuscum, C. melanocrater, C. poggei. A lectotype is designated for C. bipindense, C. cavum, C. conglobatum, C. consors, C. excavatum, C. goossensii, C. lupakense, C. tanganyikense var. microcalyx, C. triplinerve, C. welwitschii. A second-step lectotype is designated for C. silvanum. A new combination is made (Clerodendrum johnstonii var. marsabitense). Two species are new to D.R. Congo and 2 species are new to Burundi. Four taxa are endemic to D.R. Congo (C. capitatum var. vanderystii, C. capitatum var. pubitubum, C. dewittei, C. pynaertii) and one taxon is endemic to Burundi (C. fasciculatum).